2019
DOI: 10.1002/jcp.29224
|View full text |Cite
|
Sign up to set email alerts
|

miR‐218 regulates diabetic nephropathy via targeting IKK‐β and modulating NK‐κB‐mediated inflammation

Abstract: Diabetic nephropathy (DN) is a common clinically relevant complication of diabetes that is associated with damage to the capillaries, yet the etiology of this condition remains unclear. Nuclear factor-kappa B (NF-κB) activation is known to be associated with DN-related inflammation and disease progression. Recent work indicated that microRNAs are diagnostic biomarkers of DN progression associated with inflammation in the progression of DN. miR-218 is known to play key regulatory roles in certain cancers in hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…Consistent with the above findings, we also observed that miR-218 was upregulated in DKD and could reduce cell viability in HGtreated renal tubule cells, which indicated that depletion of miR-218 may protect cells from injury during the development of DKD. However, Li et al, using a rat streptozotocin-induced model of DKD and in vitro HGstimulated mouse podocytes, demonstrated that miR-218 was markedly downregulated in both model systems relative to appropriate controls [19]. We hypothesized that many factors, such as different inducers, and animal or human cells, contributed to this phenomenon.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Consistent with the above findings, we also observed that miR-218 was upregulated in DKD and could reduce cell viability in HGtreated renal tubule cells, which indicated that depletion of miR-218 may protect cells from injury during the development of DKD. However, Li et al, using a rat streptozotocin-induced model of DKD and in vitro HGstimulated mouse podocytes, demonstrated that miR-218 was markedly downregulated in both model systems relative to appropriate controls [19]. We hypothesized that many factors, such as different inducers, and animal or human cells, contributed to this phenomenon.…”
Section: Discussionmentioning
confidence: 88%
“…The mechanism of action of miRNA is mediated by binding target mRNA to inhibit mRNA translation or degrade miRNAbound mRNA, thus inhibiting protein synthesis [15]. By a literature review, it has also revealed that numerous miRNAs are involved in the inflammation of DKD, including miR-218 [16][17][18][19]. It is noted that overexpression of miR-218 can reduce renal injury in a streptozotocin-induced rat model of DKD and can inhibit inflammatory response in the high glucose (HG) induced mouse podocytes by targeting mRNA encoding IKK-b [20].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that in a DN rat model, overexpressing miR-218 was sufficient to reduce renal injury through regulating NF-κB-mediated inflammation. Moreover, they confirmed that miR-218 targets the messenger RNA (mRNA) encoding IKK-β [40]. [46].…”
Section: Characteristics Of Ncrnasmentioning
confidence: 86%
“…Regarding miR-218, Yao et al [ 22 ] reported that microRNA-218 inhibited the viability and accelerates the apoptosis in ARPE-19 cells by directly targeting RUNX2. Moreover, the experimental research showed [ 23 ] that miR-218 was markedly downregulated in diabetic nephropathy rat model, and overexpressed miR-218 markedly reduced inflammatory responses, detected by measuring the level of TNF-α, IL-6, IL-1β, and MCP-1. Previously, it [ 24 ] has been reported that lncRNA CCAT1 serves as a microRNA-218 sponge to induce Gefitinib Resistance in NSCLC by Targeting HOXA1.…”
Section: Introductionmentioning
confidence: 99%